2003
DOI: 10.1021/ac034664d
|View full text |Cite
|
Sign up to set email alerts
|

Multilabeling Biomolecules at a Single Site. 1. Synthesis and Characterization of a Dendritic Label for Electrochemiluminescence Assays

Abstract: Ultrasensitive bioanalytical assays are of great value for early detection of human diseases and pathogens. The sensitivities of immunoassays and DNA probing can be enhanced by multilabeling the biorecognition partner used for affinity-based assays. However, the bioreactivity of biomolecules is affected by a high degree of multilabeling at multiple functional sites. It is proposed that dendritic scaffoldings be used to link multiple signal-generating units to a single site with potentially minimum impact on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 46 publications
1
64
0
Order By: Relevance
“…It should be noted that, for 4, the metal-centered redox potential is more positive than that of 1, whereas the three ligand-centered redox potentials are more negative than those of 1. 18,19 The E 1/2 values of these redox processes are 1.29 V (∆E p ) 0.087 V), -1.42 V (∆E p ) 0.080 V), -1.62 V (∆E p ) 0.086 V), and -1.89 V (∆E p ) 0.088 V), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, for 4, the metal-centered redox potential is more positive than that of 1, whereas the three ligand-centered redox potentials are more negative than those of 1. 18,19 The E 1/2 values of these redox processes are 1.29 V (∆E p ) 0.087 V), -1.42 V (∆E p ) 0.080 V), -1.62 V (∆E p ) 0.086 V), and -1.89 V (∆E p ) 0.088 V), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, efforts have been made in the syntheses and demonstration of labels bearing multiple [Ru-(bpy) 3 ] 2+ units. 18,19,29 On the other hand, because the large family of [Ru(bpy) 3 ] 2+ was far from being exhausted, it is our objective to find [Ru(bpy) 3 ] 2+ luminophores with stronger ECL emission under the practical conditions. Here we report a comparative study of ECL from various [Ru(bpy) 3 ] 2+ complexes (shown in Scheme 1) with one or more mono-/ bi-substituents at 4-and/or 4′-position(s) of bipyridine ring-(s) in TPA-containing aqueous buffer solutions.…”
mentioning
confidence: 99%
“…Astruc et al examined their ability to serve as recognition elements for a variety of ions, including H 2 PO 4 -, ATP 2-, and HSO 4 - (56). The electrochemical and spectroscopic properties of metallodendrimers have been exploited to develop amperometric biosensors and DNA immunoassays (57)(58)(59). In addition, because both the photophysics and the redox behavior of the pendant chromophores or electrophores are sensitive to their environment, applications as sensors for a variety of species have been considered, such as the luminescence quenching by aromatic nitro groups mentioned earlier (37).…”
Section: Applicationsmentioning
confidence: 99%
“…5 One of the most efficient ways of signal amplification is the application of tags that are not directly detected but can catalyze a reaction that yields an easily detectable product such as a dye. 6 Another method for increasing the sensitivity of immunoassays utilizes a multilabeling technique, 7 where an antibody is labeled not at a single NH2 or COOH site, but a number of such functional groups are modified with a tag. 8 This strategy has a serious limitation because a high degree of substitution affects the specificity of antibodies.…”
Section: Introductionmentioning
confidence: 99%